Consumer Problems In India and Its Measures: Addressing challenges and solutions for Indian consumers (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The etymology of the word ‘ consumer’ indicates itsorigin from the verb ‘to consume ‘ first mentioned  in literature in its old English form‘consumed’ by wyclif in 1382.Till the sixteenth it conveyed a kind of negativemeaning , viz consumer being the one who wastes or squanders.consumer buys thegoods and services , expecting that the goods he buys  are fresh, the drugs are pure and effective ,the products are safe and work well; the price that he is charged for is fair,the water he takes is pure, the air he inhales is unpolluted,the telephonefunctions properly, his letters reach the destination in time his electricitysupply remains uninterrupted and he can travel safely in time from one place toanother. Consumer faces many problems ,for example, Variation inPrices,Adulteration,Unfair means of measurement. Misleading advertisements,Misleading and incomplete labels,Sale of inferior goods,Malpractices adopted by the manufacturers or sellers etc.